Long-term repetition priming and semantic interference in a lexical-semantic matching task: tapping the links between object names and colors - Lloyd-Jones, Toby J.; Nakabayashi, Kazuyo (Frontiers in Psychology, 2014)
Using a novel paradigm to engage the long-term mappings between object names and the prototypical colours for objects, we investigated the retrieval of object-colour knowledge as indexed by long-term priming (the benefit in performance from a prior encounter with the same or a similar stimulus); a process about which little is known. We examined priming from object naming on a lexical-semantic matching task. In the matching task participants encountered a visually presented object name (Experiment 1) or object shape (Experiment 2) paired with either a colour patch or colour name. The pairings could either match whereby both were consistent with a familiar object (e.g., strawberry and red) or mismatch (strawberry and blue). We used the matching task to probe knowledge about familiar objects and their colours pre-activated during object naming. In particular, we examined whether the retrieval of object-colour information was modality-specific and whether this influenced priming. Priming varied with the nature of the retrieval process: object-colour priming arose for object names but not object shapes and beneficial effects of priming were observed for colour patches whereas inhibitory priming arose with colour names. These findings have implications for understanding how object knowledge is retrieved from memory and modified by learning.